Snakes and Eels: The Slender Odds of Wiving Well. (June 2016) - Doyle, Charles Clay
Abstract : In A Dialogue Concerning Heresies, the character named Thomas More attributes to his father the quip that the choice of a wife resembles a man's reaching into a bag full of snakes, hoping to grasp the single eel present in the bag. Subsequent versions of the "merry saying" record many different ratios of snakes to the one eel. Some recountings, through the centuries up to recent times, have explicitly cited Thomas More or his father, John More; a great many do not. Some writers have credited the saying to other originators, in a variety of languages and countries. Eventually it came to apply to unfavorable odds that prevail in numerous concerns besides marriage. Although Thomas More's use of the saying—in reference to religious beliefs—seems to be the earliest in print, there exists the possibility that More was adapting an expression already current in oral tradition.